Da’wah Communication in Classical Malay Literature: Analyzing Islamic Values in Raja Ali Haji’s Syair Abdul Muluk - Ahmad Subiyadi; Abdullah Idi; Nurhayati Nurhayati; Mohammad Syawaludin; Husain Ibrahim (RUSYDIAH: Jurnal Pemikiran Islam, 2026)
This study aims to analyze and formulate Raja Ali Haji’s cultural da’wah communication model developed through the integration of Islamic values and classical Malay literary traditions in the Syair Abdul Muluk manuscript (1,824 stanzas). Utilizing a descriptive qualitative method supported by historical, literary hermeneutics, and cultural sociology approaches, this research explores the theological content deliberately embedded within the narrative structure of heroic fiction. The results indicate that Syair Abdul Muluk integrates 12 pillars of Islamic values encompassing theological (creed/tawakkal), sharia (worship), and moral dimensions (just leadership ethics and sharia-compliant gender emancipation). The da’wah communication model in this text exemplifies a systematic cultural da’wah strategy, where literary aesthetics serve as a channel to soften religious doctrines, making them adaptive for a traditional Malay audience. This study also uncovers a text-purification function that corrects local syncretic practices, such as shifting the function of traditional offering rituals (sesajen) in the oral tradition of Dulmuluk performances toward sharia-compliant prayers for safety (doa selamat). The implications of this study reaffirm the vital contribution of 19th-century classical literature as a methodological foundation for contemporary da’wah that is persuasive, inclusive, and prioritizes moral excellence.